FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN POSTPARTUM BLUES - Devi Endah Saraswati Saraswati (Universitas Nahdlatul Ulama Surabaya, 2018)
Childbirth is a happy moment, but there are some cases can be frightening, this is because women who give birth often experience feelings of sadness and fear that affects the emotional and sensitivity of the mother, known as postpartum blues. The purpose of this study is to know the factors - factors that affect the incidence of postpartum blues. The research design was cross sectional. The study was conducted at BPM "D" in Campurejo Village, Bojonegoro District and BPM "S" in Sukorejo Village, Bojonegoro District from January to February 2018 to 30 postpartum mothers. The study instrument used an EDPS (Edinburgh Postnatal Depression Scale) questionnaire. Data processing using Chi Square test. The results showed that the factors affecting the phenotype of postpartum blues include p value = 0,04, education with p value = 0,049, obstetric status with p value = 0,011. Factors affecting postpartum blues events include age, education, occupation, and obstetric status.